Modern non-proliferation and disarmament: Denmark and the G8 global partnership - Cindy Vestergaard (Danish Institute for International Studies (DIIS), 2009)
Denmark should use its unique expertise on radiation protection, biosafety/biosecurity and disease surveillance and develop an international control system for nuclear and biological materials in order to help smaller states prevent dangerous materials from falling into the wrong hands. A new DIIS report by Cindy Vestergaard Modern Non-proliferation and Disarmament: Denmark and the G8 Global Partnership argues that several countries in the former Soviet Union, Asia and Africa do not have the capacity nor the experience to secure the materials properly. The Danish National Institute of Radiation Protection has unique expertise in the creation of a national database which tracks the some 11.000 radiation sources in Denmark this knowhow as well as expertise from other institutions could be used to enhance world wide control and security as part of the G8 global partnership. The report notes that a focused Danish non-proliferation and disarmament program does not involve large sums of money. Rather, a 'niched' and coordinated program could be delivered for the same funding amount Denmark previously contributed but with greater effect. To date, Denmark has provided large funds through international organizations, but unfortunately hasn't used its domestic nuclear, biological and chemical expertise to gain international recognition, Vestergaard says. Instead Denmark should consider a more 'niched' non-proliferation program for the upcoming G8 summit in 2010, Vestergaard argues. The main points and recommendations of the report Modern Nonproliferation and Disarmament: Denmark and the G8 Global Partnership is available in the DIIS Policy Brief titled Denmark and Modern Non-proliferation Assistance and Disarmament.
Keywords: 300; Abrüstung; Dänemark